Do we need tax harmonization in the EU? - Alfred Boss (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
For many years there have been political intentions to harmonize tax rates in Europe. As to capital income taxation, competition is often seen to be especially harmful. Facing a high degree of international capital mobility, every country is expected to reduce its tax rate in order to attract new capital or not to lose capital allocated in the country ("race to the bottom"). It is shown that the development of capital income tax rates in the European Union (EU) and in other industrialized countries as well as the development of corporate income tax revenues do not indicate that a race to the bottom has taken place. If tax competition should become as fierce as some observers seem to fear, the arguments in favor of tax competition instead of harmonization should be kept in mind. If tax rates are cut in a process of competition, government expenditures have to be reduced; this helps to avoid waste and inefficiencies in the public sector. In addition, tax competition might help to find better tax systems, and every country could learn from the experiences of other countries. In contrast, tax harmonization would probably lead to higher taxes in the EU.
Keywords: H20; H87; 330; tax competition; tax rate harmonization; value-added taxation in the EU; capital income taxation in the EU; EU-Steuerrecht; Steuerwettbewerb; Umsatzsteuer; Kapitalertragsteuer; EU-Staaten